Study guides

☆☆

Q: What expression is equivalent to -3(x 10)?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3x-3y?

Radical (3x) = radical(x) * radical(3).

2(3x + 4) = 6x + 8 3(x - 5) = 3x - 15 6x + 8 - 3x + 15 = 3x + 23

10 + 3x

3(x-y)

Related questions

It is equivalent to 15x+10

6

3x-3y?

3x + 3x + 3x = 3* (3x) = 9x

It is an expression that is equivalent to -3x-19.

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.

Radical (3x) = radical(x) * radical(3).

-9

2(3x + 4) = 6x + 8 3(x - 5) = 3x - 15 6x + 8 - 3x + 15 = 3x + 23

It is equivalent to: 3x+6+5 = 3x+11

2(3x + 4) = 6x + 8 3(x - 5) = 3x - 15 6x + 8 - 3x + 15 = 3x + 23

10 + 3x

People also asked